Changes In Safety and Universal Precaution Practices During Covid-19 Pandemics: The Case of One Primary Health Care Center in Yogyakarta - Kezia Dewi Santoso; Martinus Sutena; Mubasysyir Hasanbasri (Jurnal Sehat Indonesia (JUSINDO), 2024)
The COVID-19 pandemic in Indonesia has adversely impacted the economy, healthcare, the environment, education, and various others aspects. In the field of healthcare, there has been a surge in the number of fatalities among medical personnel. This increase in medical personnel has rendered health workers a vulnerable group. In this case, guidelines are required to prevent and manage COVID-19 effectively, ensuring the health, safety, and productivity of healthcare workers. The objective of this study is to assess the implementation of the occupational health and safety (OHS) management system at the Tegalrejo Health Center in carrying out COVID-19 preventive measures for health workers. This research is a qualitative study employing a case study approach. The research was conducted at the Tegalrejo Health Center in Yogyakarta. There were 10 participants, including the health center’s head, administrative head, OHS team leader, infection prevention and control (IPC) team leader, COVID-19 task force leader, risk management head, 2 OHS members, an IPC member, and a nurse. Data collection methods included in-depth interviews, observation, and document review. The preparedness of health centers in facing an abrupt pandemic significantly affects the prevention of COVID-19 infection among healthcare workers. Health centers have stringent regulations that encourage healthcare workers to take preventive actions. Tegalrejo Health Center takes preventive measures against health workers from COVID-19 infection by making policies and planning Occupational Health and Safety programs adapted to pandemic conditions.